Regional vulnerability to environmental and climate change risks: A study of Odisha, India - Archisman Sardar,; Kapil Kumar Gavsker, (National Geographical Journal of India, 2023)
Climate change-induced risks and their regional implications are inevitable on land, resources, and living communities. It is a social challenge because societies are at risk at varied levels. To study the relationship between regional vulnerability to climate change risks is to give a telescopic view from below. The state of Odisha, located along the eastern coastal region of India, is selected for the present study. Considering natural, demographic, and economic aspects, selected indicators at the district level are applied in the study. In the context of the functional relation to climate change risk, the indicator score is standardized, the vulnerability index calculated, and districts are categorized based on the vulnerability scale. The analysis shows remarkable spatial variations in higher and lower vulnerability districts in the state. These spatial contrasts are associated with the development pattern of the state. Most vulnerable are in the western and southern interior and a few in the north compared to the low vulnerability districts located along the eastern coast and central part of the state. The regional vulnerability perspective thus offers insights and contributes towards strengthening development strategy, responses, and policymaking for tackling climate change risks and the implications and concerns across the region.